Treatment of Chronic Periodontitis in One Visit - Asrorovna, Xolboyeva Nasiba; o‘g‘li, Temirov Muhammad Dilshod (American Journal of Biology and Natural Sciences, 2025)
This article analyzes the clinical effectiveness of single-visit treatment strategies for chronic periodontitis, emphasizing their advantages, limitations, and long-term outcomes. The approach is based on comprehensive mechanical debridement, adjunctive antimicrobial therapy, and immediate periodontal stabilization within one clinical appointment. The work evaluates patient response, periodontal index changes, microbial reduction, and overall healing dynamics following single-visit therapy, providing an evidence-based assessment of its practicality. This study provides a detailed assessment of the one-visit approach to managing chronic periodontitis, focusing on its therapeutic potential, biological impact, and clinical practicality. The work explores the treatment-related changes that occur when full-mouth debridement, infection control, and tissue stabilization are performed during a single appointment. Special attention is given to inflammatory reduction, periodontal tissue recovery, microbial suppression, patient-reported outcomes, and the sustainability of results over time. The analysis highlights the benefits of consolidating therapy into one visit and evaluates how this method influences healing efficiency and long-term periodontal health.